New Section 375 Indian Penal Code (IPC) Confusion and Controversies - Gupta, B D; Chavali , K H (Journal of Indian Academy of Forensic Medicine, 2016)
The 2012 Delhi gang rape of a college student, infamously referred to as the Nirbhaya incident  has forced the law makers of the country to sit up and make long-pending amendments to the sections of  the Indian Penal Code (IPC) that deal with sexual violations. The result was that the Criminal Law  Amendment Act was passed in 2013 in which the existing Section 375 of the IPC has been revamped  and a new section substituted in its place.  This paper compares certain aspects (few) of the old Sec 375 IPC and new Sec 375 IPC. It also  deals with the controversies and confusion arising out of the new IPC 375 and existing IPC 377. It neither  reviews the whole criminal amendments Act 2013 nor does it review all aspects of IPC 375. This paper  also deals with a situation (third person) where the new IPC 375 is silent.
Keywords: IPC 375 New; IPC 375 Old; IPC 377; Difficulties in interpretation